Understanding different car users as starting point for future mobility concepts – A co-creation approach. (December 2021) - Gebhardt, Laura
Highlights: Empirical study that examine everyday life mobility of car users. Presentation of mobility logics and requirements that underlay users' travel behavior. Qualitative, participatory co-creation approach. User centered hints for target-group-specific actions in urban and transport planning. Abstract: The car is still the most used mean of transport in many countries around the world. To reach sustainability, though, reducing motorized transport is a necessity. It is therefore important to understand and address the perspective of car users when developing alternative mobility concepts. Debates around new mobility concepts are often led from a quite technical perspective. When dealing with transformation processes in mobility, however, we are not only confronted with technical challenges, but also with questions regarding the people who are concerned. Therefore, this article aims to contribute to the current discussion by examining mobility logics and requirements that underlie users' travel behavior. The empirical study examines everyday life mobility using a qualitative, participatory approach. This transdisciplinary approach brings together scientific and non-scientific bodies of knowledge and is situated at the interface of technology development and sociological mobility research. The results indicate that visions of future concepts are strongly shaped by experiences and expectations related to users' lives. This knowledge forms a valuable basis for developing target-group-specific policies and measures in urban and transport planning.